Social of Women and Girls in Our Country-Improvement of Political and Social Activity Factors - et. al., Ismailova Zuxra, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The article gives an idea of the factors that improve the activity of women in the socio-political spheres, the opportunities that high organizations give to women, the conditions, the activity and initiative of women in the life of a separate society and the state, the strengthening of the formation and well-being of the family with its effective efforts, the awards given to